Hybridization between two cryptic filamentous brown seaweeds along the shore: analysing pre‐ and postzygotic barriers in populations of individuals with varying ploidy levels. Issue 13 (8th April 2017) - Montecinos, Alejandro E.; Guillemin, Marie‐Laure; Couceiro, Lucia; Peters, Akira F.; Stoeckel, Solenn; Valero, Myriam
Abstract: We aimed to study the importance of hybridization between two cryptic species of the genus Ectocarpus, a group of filamentous algae with haploid–diploid life cycles that include the principal genetic model organism for the brown algae. In haploid–diploid species, the genetic structure of the two phases of the life cycle can be analysed separately in natural populations. Such life cycles provide a unique opportunity to estimate the frequency of hybrid genotypes in diploid sporophytes and meiotic recombinant genotypes in haploid gametophytes allowing the effects of reproductive barriers preventing fertilization or preventing meiosis to be untangle. The level of hybridization between E. siliculosus and E. crouaniorum was quantified along the European coast. Clonal cultures (568 diploid, 336 haploid) isolated from field samples were genotyped using cytoplasmic and nuclear markers to estimate the frequency of hybrid genotypes in diploids and recombinant haploids. We identified admixed individuals using microsatellite loci, classical assignment methods and a newly developed Bayesian method ( XPloidAssignment ), which allows the analysis of populations that exhibit variations in ploidy level. Over all populations, the level of hybridization was estimated at 8.7%. Hybrids were exclusively observed in sympatric populations. More than 98% of hybrids were diploids (40% of which showed signs of aneuploidy) with a high frequency of rare alleles. The near absence of haploid recombinant hybrids demonstrates that the reproductive barriers are mostly postzygotic and suggests that abnormal chromosome segregation during meiosis following hybridization of species with different genome sizes could be a major cause of interspecific incompatibility in this system. Abstract : see also the Perspective by Johannesson